49, XXXYY: Parental Origin, Occurrence, and Clinical Phenotypes - Yufang Du; Liangrong Liao; Xianda Wei; Yunting Ma; Meizhen Shi; Chunyan Li; Juliang Liu; Wenting Lin; Hao Zeng; Shaoke Chen; Baoheng Gui (Genetics Research)
49, XXXYY is a rare form of sex chromosomal aneuploidy that has been reported in 11 cases worldwide. The parental origin of the extra sex chromosomes and the specific clinical features of this condition remain unclear. We recruited a case with 49, XXXYY and performed genome-wide copy number variation analysis using next-generation sequencing. In addition, the parental origin of the extra sex chromosomes was determined through short tandem repeats (STRs) locus genotyping. Furthermore, a comprehensive review and comparison of clinical phenotypes were conducted among 12 cases with 49, XXXYY. The patient exhibited a karyotype of 49, XXXYY without any mosaic patterns. No pathogenic microdeletions or microduplications (> 100 kb) were identified in autosomes 1–22. Analysis of the STR loci revealed that two of three X chromosomes originated from father. This suggests that the nondisjunction of chromosomes X and Y during stages I and II of meiotic spermatogenesis led to the production of an abnormal sperm with XXYY. Subsequently, fertilization of a normal oocyte with this abnormal sperm resulted in an abnormal zygote with pentasomy XXXYY. The main clinical features observed in these cases included varying degrees of mental retardation, minor facial dysmorphology, and gonadal or endocrine abnormalities. In conclusion, 49, XXXYY is a rare chromosomal disorder characterized by mental retardation and facial dysmorphology. Nondisjunction of chromosomes X and Y during stages I and II of meiotic spermatogenesis is a critical factor contributing to the development of this abnormal karyotype.